"More than just another physical activity program": exploring the GUM program for at-risk adolescent girls. (22nd March 2021) - Hargreaves, Nicole; Forneris, Tanya; Sabiston, Catherine; Berg, Stephen; Kowalski, Kent; Ferguson, Leah; Caperchione, Cristina
Abstract: Physical activity (PA) levels among adolescent girls continue to steadily decline, especially for those classified as 'at-risk'. To mitigate these trends, Girls United and on the Move (GUM) was created as a dual-component PA and psychosocial program. The primary purpose of this study was to explore participant experiences within GUM, with a secondary purpose of qualitatively informing future PA programs for 'at-risk' adolescent girls. Semi-structured interviews (N = 30) were conducted with a purposeful sample of girls from the GUM program. An inductive thematic analysis was utilized to analyze verbatim transcripts. Two themes were generated from the data: 1) Girls uplifting girls, outlining the importance of a girls-only environment and introducing opportunities for alternative PAs, and 2) finding balance between the physical and psychological, detailing the importance of the dual-component program. These findings provide support for the acceptability of an integrated psychosocial and PA program for at-risk adolescent girls.